2011
DOI: 10.1152/jn.00869.2010
|View full text |Cite
|
Sign up to set email alerts
|

Colored context cues can facilitate the ability to learn and to switch between multiple dynamical force fields

Abstract: We tested the efficacy of color context cues during adaptation to dynamic force fields. Four groups of human subjects performed elbow flexion/extension movements to move a cursor between targets on a monitor while encountering a resistive (Vr) or assistive (Va) viscous force field. They performed two training sets of 256 trials daily, for 10 days. The monitor background color changed (red, green) every four successful trials but provided different degrees of force field context information to each group. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 65 publications
1
54
0
Order By: Relevance
“…In the force field adaptation literature, a concept similar to the specificity of practice is often studied by evaluating the effect of matching various contextual cues to different pattern of force fields that are normally impossible to learn simultaneously because they require opposite motor strategies (e.g., clockwise versus counterclockwise perturbation during reaching movements). Reduced interference when each force field is associated with a different contextual cue is interpreted as a proof that the contextual cues allow the independent coding of motor skills involved for each adaptation [15, 26, 27]. Different contextual conditions can be manipulated to affect performance during retention tests and can be analyses in relation to the specificity of practice hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the force field adaptation literature, a concept similar to the specificity of practice is often studied by evaluating the effect of matching various contextual cues to different pattern of force fields that are normally impossible to learn simultaneously because they require opposite motor strategies (e.g., clockwise versus counterclockwise perturbation during reaching movements). Reduced interference when each force field is associated with a different contextual cue is interpreted as a proof that the contextual cues allow the independent coding of motor skills involved for each adaptation [15, 26, 27]. Different contextual conditions can be manipulated to affect performance during retention tests and can be analyses in relation to the specificity of practice hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…These contexts include whether the opposite arm is stationary or moving (Nozaki et al, 2006), the kinematics of the opposite arm (Howard et al, 2010;Yokoi et al, 2011Yokoi et al, , 2014, or whether the movement plans are adapted for the same movement (Hirashima and Nozaki, 2012). However, it is largely unknown why simultaneous adaptation is possible in some cases (Cothros et al, 2009;Addou et al, 2011;Howard et al, 2012) and impossible in other cases (Karniel and Mussa-Ivaldi, 2002;Shadmehr et al, 2005). The present study demonstrated that the formation and retrieval of distinct motor memories could be evaluated using the changes in the MEP between baseline and test sessions.…”
Section: Modulation Of Corticospinal Excitability Depending On Contexmentioning
confidence: 99%
“…Novelties introduced in that work included training "miniblocks" before randomswitching phases, and different lengths of miniblock have been explored over different sessions. In motor adaptation it has been shown that frequent and random switching between contexts increases the learning (Osu et al 2004;Wada et al 2003), as perhaps does reduced movement dimensionality (Addou et al 2011). This repeat exposure to random switching of contextual adaptation may have increased our previous subjects' prior likelihood of responding to purely visual cues.…”
Section: Can Feature-based Contextual Cues Be Trained?mentioning
confidence: 99%